Health-related quality of life and associated factors among type 2 diabetic adult patients in Debre Markos Referral Hospital, Northwest Ethiopia. Issue 8 (August 2022) - Wonde, Tewodros Eshete; Ayene, Tessema Reta; Moges, Nurilign Abebe; Bazezew, Yibelu
Abstract: Health-related quality of life (HRQOL) is a multifaceted concept that is strongly impacted by Type II diabetes in developing countries. The majority of studies indicate diabetes mellitus prevalence without looking at people's quality of life. This study was conducted using an Institution-based cross-sectional design in Debre Markos Referral Hospital from March 03 to March 31, 2020. We evaluated HRQOL using the WHO quality of life BREF and data were obtained through face-to-face interviews. We used a systematic random sampling technique to select study participants. Data were entered into Epi data version 3.1 and exported to STATA version 14.0. Candidates for multivariable analysis were variables with a P-value less than 0.25 in the bivariable analysis and P-value less than 0.05 were considered to declare a statistically significant association. The final model was tested for its goodness of fit using Hosmer and Lemeshow's statistics. The analysis included a total of 368 adult individuals with type II diabetes and 206 (56%) had a good HRQOL. Being male (AOR = 4.28, 95%CI:2.36, 7.78), having duration of disease of more than 59 months (AOR = 2.93, 95%CI:1.61, 5.34), doing a physical exercise (AOR = 2.33, 95%CI:1.34, 4.05) and got counseling (AOR = 3.33; 95%CI:1.82, 5.94) were directly associated with good HRQOL whereas the presence of diabetic complications (AOR = 0.46, 95%CI:0.26, 0.80), comorbidity (AOR = 0.45; 95%CI:0.25, 0.84) and drinking alcohol (AOR = 0.27, 95%CI:0.16, 0.48) had an inverse relationship with good HRQOL. More than half of type 2 diabetic adult patients had a good HRQOL. Being male, drinking alcohol, getting counseling, doing physical exercise, absence of diabetic complications, and comorbidity and long duration of disease were predictors of good HRQOL. Therefore, avoiding drinking alcohol and promoting physical exercise and counseling should be encouraged. Abstract : Quality of life; type 2 diabetes mellitus; Debre Markos.